How Cyclical Is the User Cost of Labor? - Marianna Kudlyak (Institute of Labor Economics (IZA), 2024)
In employment relationships, a wage is an installment payment on an implicit long-term agreement between a worker and a firm. The price of labor that impacts firm's hiring decisions, instead, reflects the hiring wage as well as the impact of economic conditions at the time of hiring on future wages. Measured by the labor's user cost, the price of labor is substantially more pro-cyclical than the new-hire wage or the average wage. The strong procyclicality of the price of labor calls for other forces for cyclical labor demand to explain employment fluctuations.
Keywords: E24; E32; J30; J41; J63; J64; 330; user cost of labor; wages; cyclicality; wage rigidity; unemployment